Molecular epidemiology and disease severity of influenza virus infection in patients with haematological disorders - Ünal, Silan; Schnitzler, Paul; Giesen, Nicola; Wedde, Marianne; Dürrwald, Ralf; Tabatabai, Julia (Journal of medical virology, 2023)
Influenza virus infection is a common cause of self-limiting respiratory tract infection (RTI), however immunocompromised patients are at an increased risk for a severe course of disease or fatal outcome. We therefore aimed to gain a better understanding of the molecular epidemiology of influenza viruses from patients with haematological disorders and their impact on the clinical course of disease. Molecular analysis using polymerase chain reaction (PCR) of nasopharyngeal swabs was performed for influenza virus in haematological patients at the Heidelberg University Hospital. Clinical data was evaluated to identify associated risk factors. For phylogenetic analysis, the hemagglutinin (HA) gene was sequenced. Out of 159 influenza positive patients, 117 patients developed upper RTI (influenza A: n = 73; influenza B: n = 44). Lower RTI was observed in n = 42 patients (26%), n = 22/42 patients developed severe disease and n = 16/159 (10.1%) patients died. Risk factors for lower RTI were nosocomial infection (p = 0.02), viral shedding for ≥14 days (p = 0.018), IgG levels <6 g/dL (p = 0.046), bacterial/fungal co-infections (p < 0.001). Risk factors for fatal outcome were age ≥65 years (p = 0.032), bacterial/fungal (p≤0.001) co-infections and high viral load (p = 0.026). Sequencing of the HA gene (n = 115) revealed subtype A(H3N2) (n = 46), A(H1N1)pdm09 (n = 24), B/Victoria (n = 34), B/Yamagata (n = 11). There was no correlation between influenza (sub)type and lower RTI. Influenza infection in haematological patients is associated with significant morbidity and mortality, the risk for aggravating co-infections, prolonged viral shedding and nosocomial transmission emphasizing the need for infection control.
Veröffentlicht: 30. Mai 2023
Gesehen am 28.09.2023